Real Time Productivity Monitoring System for Small and Medium Size Manufacturing Industry - Phaik-Ean, Wong; Lee Abdullah, Nasuha; Idrus, Rosnah; Keikhosrokiani, Pantea (International Journal of Engineering and Technology, 2018)
This paper attempts to propose a real-time knowledge management system to monitor productivity for production lines of small and Â medium size enterprises (SME). The proposed system hopes to empower managers in meeting the target of daily production output. The uniqueness is it provides real time productivity level to enhance visibility and control in the production lines. The system automates the process of data collection by using bar code scanners at the input and output stations. Productivity is calculated based on cycle time of each product and display in real time. Colour coded display indicating productivity level enables the line foreman to take immediate Â action. Apart from that, it can also send alert in the form of Whatsapps messages to relevant personnel in case of loss time issues. The system consists of two main modules, which are, data collection module and reporting module. It is developed as a web-based knowledge management system to ease setup, access, and maintenance to facilitate future upgrade into mobile application. The system can be implemented in any production line to monitor the line performance and helps to reduce loss time by providing an instantaneous response to solve issues.Â Â